Culture of care: the question of animal agency in laboratory animal science - Ameli, Katharina; Krämer, Stephanie (Frontiers in Veterinary Science, 2024)
Based on empirical qualitative interviews and previous research, Culture of Care describes a complex mosaic of mutually dependent core categories. The perception and understanding of the agency of laboratory animals play subordinate roles. The aim of this qualitive research was to analyze the perception and understanding of animal agency among experts in the field of animal-based research. It became apparant that animal agency as a (theoretical) construct does occur in the theoretical reception of the Culture of Care model. However, it is not conclusively established in everyday practice. Rather, the results led to the assumption that strategies have been developed to largely eliminate laboratory animals' agency. One recommendation would be an integration of animal agency through practicing multispecies ethnography in laboratory animal sciences.